ENERGY-SAVING DEVICE FOR TEMPORARY DITCH PRODUCTION - J.U.Ruzikulov; A.A.Jurayev; Kh.Nuriddinov; D.U.Ruzikulova (TADQIQOTLAR.UZ, 2024)
Absract: The article describes the research on the improvement of the temporary ditching device. In order to reduce the traction resistance of the channel and improve the channel quality, two straight discs are installed in front of the channel. During the excavation, the slope of the temporary ditch was maintained at the required level due to the partial disintegration of the soil layer due to the rotational movement of the disk, and the issue of maintaining the uniformity of the temporary ditch side wall was discussed.